Stamps of the Italian Legion I on bricks and roof tiles from Novae - Sarnowski, Tadeusz; Trynkowski, Jan (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes stamps of Legio I Italica with depictions of ships found on bricks and roof tiles in Novae. The problem concerns the meaning and function of these unusual representations. The aim of the work is their iconographic and chronological interpretation. The authors apply archaeological and comparative analysis. The most important results indicate that these stamps appear mainly in construction contexts and are probably dated to the 2nd century AD. The ship depictions may refer to transport or military activity of the legion. The conclusion is that the stamps testify to building activity and symbolic aspects of the unit’s functioning.